2012
DOI: 10.1016/j.immuni.2012.03.023
|View full text |Cite
|
Sign up to set email alerts
|

The Adaptor SAP Controls NK Cell Activation by Regulating the Enzymes Vav-1 and SHIP-1 and by Enhancing Conjugates with Target Cells

Abstract: The adaptor SAP, mutated in X-linked lymphoproliferative disease, has critical roles in multiple immune cell types. Among these, SAP is essential for the ability of natural killer (NK) cells to eliminate abnormal hematopoietic cells. Herein, we elucidated the molecular and cellular bases of this activity. SAP enhanced NK cell responsiveness by a dual molecular mechanism. It coupled SLAM family receptors to the kinase Fyn, which triggered the exchange factor Vav-1 and augmented NK cell activation. SAP also prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
204
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(215 citation statements)
references
References 58 publications
11
204
0
Order By: Relevance
“…Ly108, but not CD84 or SLAM, inhibits Ag-specific T cell adhesion to both B cells and DCs It has recently been shown that, in the absence of SAP, SLAMF molecules such as Ly108 are associated with inhibitory phosphatases and dampen Ag-specific T-B adhesion (36,37,42,43). To examine whether the inhibitory function is a unique property of Ly108, we retrovirally transduced SLAM, CD84, and two main Ly108 isoforms into either WT or SAP KO T cells (Fig.…”
Section: Sap Is Required For Optimal T-b Adhesion Soon After Ligand Rmentioning
confidence: 99%
See 1 more Smart Citation
“…Ly108, but not CD84 or SLAM, inhibits Ag-specific T cell adhesion to both B cells and DCs It has recently been shown that, in the absence of SAP, SLAMF molecules such as Ly108 are associated with inhibitory phosphatases and dampen Ag-specific T-B adhesion (36,37,42,43). To examine whether the inhibitory function is a unique property of Ly108, we retrovirally transduced SLAM, CD84, and two main Ly108 isoforms into either WT or SAP KO T cells (Fig.…”
Section: Sap Is Required For Optimal T-b Adhesion Soon After Ligand Rmentioning
confidence: 99%
“…Several SLAMF receptors in NK cells were found to inhibit cytotoxicity when SAP and SAP-related adaptors are absent (33)(34)(35), leading to the notion of "switch" functions for SAP family adaptors in that they may physically or functionally compete with negative signaling modules associated with SLAMF receptors, and thereby convert inhibitory SLAMF functions into stimulatory actions (16). In support of this switching model, Veillette and colleagues (36) have shown that SAP simultaneously couples Fyn kinase to and uncouples lipid phosphatase SHIP-1 from SLAMF receptors in NK cells.…”
mentioning
confidence: 99%
“…2014. 44: 1526-1534 Innate immunity 1531 activation, a crucial effector of 2B4-mediated inhibition is represented by SHIP-1 (and possibly SHIP-2), which negatively regulates downstream signals such as PLC-γ-mediated Ca 2+ fluxes [14,43]. According to our observation, in SAP −/− mice, members of the SLAM receptor family have been shown to inhibit NKG2D that, different to humans, associates with both DAP10 and DAP12 [45,46].…”
mentioning
confidence: 74%
“…SLAM family receptors, principally expressed by hematopoietic cells, have Ig-like extracellular domains involved in homotypic (e.g., SLAM-SLAM) or heterotypic interactions (e.g., 2B4-CD48). Engagement of SLAM family receptors by self family ligands results in tyrosine phosphorylation of their immunoreceptor tyrosine-based switch motifs and the subsequent recruitment of SAP is thought to regulate signaling by two distinct mechanisms: 1) SAP transduction of signaling by binding the tyrosine kinase Fyn and protein kinase Cu (25,26,28,29); and 2) SAP inhibition of signaling by sterically hindering the docking of SH2 domain-containing phosphatases 1 and 2 and SHIP-1 (25,26,(30)(31)(32)(33). Thus, the absence of SAP may negate positive signaling and reinforce inhibitory signaling by SLAM family receptors.…”
Section: Il-17-secreting T Cells Was Shown To Be a T Cell-intrinsic Rmentioning
confidence: 99%